Aspects of the analytical ultracentrifuge determination of the molar mass distribution of polysaccharides - Harding, Stephen E.; Adams, Gary G.; Gillis, Richard B.; Almutairi, Fahad M.; Morris, Gordon A. (Springer, 2016)
Molar mass or ‘molecular weight’ is one of the most fundamental parameters describing a macromolecule. Because of their polydisperse nature, polysaccharides are usually described by distributions of molar mass. SEC-MALS (size exclusion chromatography coupled to multi-angle light scattering) is often a convenient method of choice, but there are many instances where it is unsuitable. Modern AUC (analytical ultracentrifuge) methods provide a valuable alternative – now easier to use than before – and, after briefly reviewing some older procedures, we highlight two recently published and complementary methods, namely, the ‘Extended Fujita’ approach for the analysis of sedimentation velocity data and SEDFIT-MSTAR for the analysis of sedimentation equilibrium data. Nonideality needs to be considered and can be dealt with in a standard way. These methods can also indicate if associative phenomena are present, which can then be quantified using more complex AUC algorithms.